Enhancing catalytic performance of zeolite-supported CuO in glycerol valorization for acrylic acid production - Iman Abdullah; Gemalangi Aida Sri; Muhammad Habiburohman; Fatimah Tresna Pratiwi; Maharani Dewi Solikhah; Yuni Krisyuningsih Krisnandi (Heliyon)
The utilization of glycerol as a fundamental ingredient in the synthesis of valuable chemicals such as acrylic acid holds significant promise, particularly due to the abundant availability of glycerol as a renewable resource within the palm oil industry. Glycerol conversion into acrylic acid can be achieved through various methods, one of which involves a dehydration-oxidation reaction facilitated by a bifunctional catalyst. In this study, we synthesized CuO-modified zeolite (CuO/HY) for glycerol valorization through a one-pot process. The HY zeolite, chosen as the support material, exhibits commendable surface area, thermal stability, and Bronsted acid sites within its framework, which are essential for catalyzing the glycerol dehydration reaction. Concurrently, the copper oxide introduces redox sites crucial for oxidizing acrolein, an intermediate in the production of acrylic acid. Analysis via scanning electron microscopy (SEM) revealed an even distribution of CuO on the HY support, forming spherical particles. Surface area analysis (SAA) indicated a reduction in the surface area of HY zeolite upon impregnation with CuO, suggesting the filling of HY zeolite pores with CuO. The catalytic glycerol conversion reactions were conducted with variations in reaction time, catalyst loading, and the H2O2 addition technique as the oxidant. Best reaction conditions were achieved using a CuO(3 %)/HY catalyst, with a dehydration duration of 3 h followed by a subsequent oxidation step for another 3 h, giving an acrylic acid yield of 35.2 %.